POTENSI LESTARI DAN STATUS PEMANFAATAN IKAN TONGKOL (Auxis thazard) DI PERAIRAN MALUKU TENGAH: Maximum Sustainable Yield (MSY) and Utilization Status of Mackerels Tuna in Central Maluku Waters - Waileruny, Welem; Saidi, Rifan; Matrutty, Delly DP (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
Fishery resources are open access and often considered as common property. This can lead to a decrease in the quality of fish resources and economic rents. This study aims to calculate the maximum sustainable yield (MSY) and to determine the exploitation status of mackerel tuna (Auxis thazard) in Central Maluku Regency water. Analysis of MSY was conducted using the Walter Hilborn and Schaefer models. It is revealed that the main fishing gear for mackerel tuna fishing in Central Maluku is purse seine which in the MSY analysis are classified as standard fishing gear. The results show that the maximum hMSY and eMSY are 17,329 tons/year and 3,055 trips/year respectively. The utilization status is at the fully-exploited level. Keywords: Fully-exploited of mackerel tuna, mackerel tuna, maximum sustainable yield, production of mackerel tuna, model Schaefer.